Evaluating Risk Management Practices in Fitness Centers: Perspectives from Facility Managers - Eraslan, Ali; Çimen, Zafer (Acta Scientiae et Intellectus, 2025)
This study aimed to evaluate the risk management practices in fitness facilities in Turkey from the perspective of facility managers. The study was designed as a general survey research, one of the quantitative research methods. The study participants comprised 263 managers working in Turkey’s three most prominent cities. As a data collection tool, "The Risk Management Scale in Health and Fitness Facilities" developed by researchers was used. As a result, it is seen that the managers have high scores for risk management practices in their facilities in all sub-dimensions. Their facilities’ highest risk management practices are in member services, structure, and design, then policy, respectively. It is determined that there are positive and high-level relations between the most policy-oriented practices of facility managers regarding risk management, followed by their practices towards structure and design and member services.